Relativistic mono-energetic transport coefficients in hot plasmas - Marushchenko, I.N.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2013)
Relativistic mono-energetic drift kinetic equation for hot toroidal plasmas is analyzed. For compatibility with non-relativistic description, non-canonical thermodynamic forces with the additional temperature-dependent term in the first thermodynamic force were introduced. The transport coefficients were defined as a convolution of monoenergetic transport coefficients with Maxwell-Jüttner distribution function and corresponding weight function.